HUBUNGAN KEKERABATAN BAHASA JAWA (KARANGGENENG) DAN BAHASA MADURA (PAMEKASAN) - Yessy Soniatin; Ajeng Widyaningsih (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The study discusses the Javanese and madura dialects of relations to see how Javanese and karenial dialects relate to madura and pamekasan dialects with a focus on kinship and varied forms of cognitive words between the two languages. The aim of this study is to explain a variety of lexicon that hasa similarity in form and meaning between Javanese and madura, and to describe the Javanese and madura kinship. The research data source is both Javanese and madura. Data collection techniques using lexicon and collection of 15 vocabularies asa gloss or basis. At the bottom of five (figure five), in Javanese becomes limo while madura is lema. In this case, vocal mail I and e. data analysis by comparing the vocabulary and noting the degree of the resemblance. The methods used are quantitative and descriptive qualitative approaches between Java and madura. According to the study, lexicon figures on the percentage of relatives between the Javanese and the madura language groups indicate that the kinship belongs to the language family (stock). In the Javanese group there was found a percentage of kinship that indicates the family group (family). The relative connections between the related languages are also supported by a variety of phonemies in some cognitive vocabularies of both vowels and consonants.